Analyzing the Effects of the Covid-19 Pandemic on University Students' Academic Performance Administration: A Post-Pandemic Assessment - Mahek Arshad; Muhammad Ajmal; Yasir Riady (CV Media Inti Teknologi, 2025)
Background of study: Covid-19 disease has significantly impacted all characteristics in life worldwide. Higher education is encountering substantial problems throughout the diverse industries impacted. This transition has resulted in significant implications, especially for the students' in education performance. Aims and scope of paper: This learning aimed to examine the effect of the Covid-19 on university students' academic routine and to assess the problems posed by the adoption of online learning practices during this period. The study also seeks to provide remedies by creating conceptual models to mitigate the effects of these difficulties in the future. Methods: This study applied a qualitative methodology to analysed the textual material and employed a fundamental quantitative methodology for doing descriptive analysis that corroborates the findings. A self-administered questionnaire was created. The study employed purposive sampling, yielding a total of 106 respondents. Students encountered various obstacles, including inadequate assistance to adjust to the alterations in their education resulting from COVID-19. Results: They faced insurmountable workloads that were untenable without sufficient assistance from educators. Moreover, challenges included inadequate computer literacy, absence of energy and internet access at home, and sluggish connection speeds exacerbated their learning experiences, ultimately affecting their academic achievement. Universities are advised to prioritize the allocation of training and resources to adeptly handle analogous situations in the future. Conclusion: Educators should be provided assistance in developing interactive online learning resources and materials for institutions of higher education. Establishing and maintaining efficient communication techniques with management, staff, educators, and students is crucial for ensuring that all parties are informed and updated regarding subsequent phases of the transition and ongoing training support.